(untitled) (Bangladesh Journal of Zoology, 2013)
The prevalence of head lice (Pediculus humanus capitis) infestation was studied among the children (1 to 7 years) in the area of Mirpur Bihari Camp, Mirpur-11, Dhaka. A total of 300 children was examined from February 2011 to January 2012 and 59.67% prevalence of head lice infestation was observed. The prevalence of pediculosis was significantly higher (p<0.05) in seven years aged children and the prevalence was significantly (p<0.05) higher in girls (72.62%) than boys (43.18%). School going children had higher (p<0.05) prevalence compared to preschool group. According to socioeconomic status, head lice infestation occurred almost equally in all social classes. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14310 Bangladesh J. Zool. 40(2): 175-181, 2012